Active viscous damping system for control of MDOF structures. - Ribakov, Y. (Earthquake engineering & structural dynamics.)
The developmental and applications of a supplemental viscous damping device with active capacity are described. The system of the dampers defined as active viscous damping system (AVDS) is presented herein. Structural control principles define here as active control theory (ACT) are used to obtain the control forces at each time step during an excitation. Control of the damping forces is possible due to a mechanical structure of the proposed AVDS and do not require the input of large power and energy. This system can be efficiently used to enhance the damping of a structure without adding in stiffness and strength. The added damping forces can be adjusted in a wide range. Its efficiency is demonstrated by a numerical simulation of a seven storey building subjected to earthquakes. The simulation shows that the behaviour of the damped structure with the AVDS is significantly improved compared to that of an uncontrolled system. Moreover, the response is better than that of adding either passive viscous dampers or electrorheological damping devices.